PENGEMBANGAN AGROWISATA PADI SAWAH BERBASIS PERTANIAN BERKELANJUTAN DI KECAMATAN MAUROLE - Imaculata Fatima (AGRICA, 2017)
Development of Rice Agrotourism Based On Sustainaable Agriculture in Maurole District. District Maurole has become one of the world's tourist destination screen sailing. Consequently, the community of Maurole District is required to provide various tourist attractions that served to tourists, including tourist attractions of rice fields. Tracing its history, tourist attractions in Maurole are available due to screen tours and benefits for farmers and local communities is not optimal. Considering the needs of farmers and the community needs to be fulfilled continuously, and the welfare must be realized, the direction of development of tourist attraction developed into agrotourism. Agrotourism is an alternative in development that leads to sustainable agriculture because its activities require farmers to conduct cultivation and conservation continuously. In addition, the principle of agronomic development based on sustainable agriculture refers to environmental balance in the long term that is beneficial to local communities, the utilization of non-destructive resources, and the benefits of social, economic, and cultures manifested well. However, empirically, agriculture-based sustainable agrotourism is not well understood in terms of knowledge, attitude, and behavior patterns of farmers, and the Maurole community, whose scope includes the concept, sustainable agronomic-based agrotourism, the actions that need to be done, and the benefits for tourists and the community in the long run. The argument encourages this important article to be socialized to provide an understanding for managers, communities, and other stakeholders in the implementation, so that more interested tourists and in turn the welfare of local communities and society generally can be guaranteed.